HAZARDS AND RISKS IN AGRICULTURE: THEORETICAL AND FUNDAMENTAL APPROACHES - Mo‘minov Muslimbek Mirzoxid o‘g‘li (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article studies the theoretical foundations of hazards and risks in agriculture. In particular, the classification of risks based on natural-climatic, economic, institutional and social factors, their impact on farmers and peasant farms is analyzed in depth. Advanced theoretical approaches and international experiences on the topic are considered in a comparative manner, and the possibilities of their use in the conditions of agriculture of Uzbekistan are assessed. The importance of scientific and theoretical approaches to reducing uncertainties and managing risks is also revealed. The article puts forward scientifically based conclusions about the need to ensure the sustainability of agriculture, rational use of resources and take into account risk factors in decision-making.